Post-traumatic Stress Disorder in Victims of Sexual Assault With Pre-assault Substance Consumption: A Systematic Review - Gong, An Tong; Kamboj, Sunjeev K.; Curran, Helen Valerie (Frontiers in Psychiatry, 2019)
Background. Post-traumatic stress disorder (PTSD) and substance consumption commonly co-occur in victims of sexual assault. Substance consumption can occur pre- and/or post-assault. Pre-assault substance consumption may have an impact on the subsequent development of PTSD. This review aims to provide an overview of current understanding of the effects of acute substance intoxication and chronic pre-assault problematic substance use on symptoms of PTSD amongst individuals who were victims of sexual assault. Methods. PsycINFO, EMBASE, and MEDLINE were searched using terms related to PTSD, sexual assault, and substance consumption. This yielded 2121 articles, 268 of which were retrieved for more detailed evaluation and thirteen of these met inclusion criteria and were appraised in full. Results. Overall, the reviewed papers supported our hypothesis that acute substance intoxication and chronic pre-assault problematic substance use are associated with fewer initial PTSD symptoms but less improvement over time, resulting in slower overall PTSD recovery. They also highlighted post-assault characterological self-blame and negative social reactions as mediators of recovery in the context of pre-assault substance consumption. Conclusions. Acute substance intoxication and chronic pre-assault problematic substance use appear to have an impact on the development of PTSD symptoms amongst victims of sexual assault. The importance of developing early interventions and routine screening and assessment for PTSD and pre-assault substance consumption is emphasized. The limited research on male victims and on substances other than alcohol is highlighted.